2017
DOI: 10.1161/jaha.116.005306
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Features of Childhood Myocarditis: A Nationwide Study in Finland

Abstract: BackgroundEpidemiology of myocarditis in childhood is largely unknown. Men are known to have a higher incidence of myocarditis than women in adults aged <50 years, but whether this is true by sex in pediatric age groups is unknown. We set out to study the occurrence and potential sex differences of myocarditis in a general pediatric population.Methods and ResultsData of all hospital admissions with myocarditis in Finland occurring in patients aged ≤15 years from 2004 to 2014 were collected from a mandatory nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 30 publications
(96 reference statements)
6
81
3
4
Order By: Relevance
“…As supporting independent data, a Finnish study on childhood myocarditis also demonstrated relative low occurrence of in-hospital death and HTx (1.9%) among all children admitted with AM. 29 Differences in patient cohorts and study design may explain, at least in part, the discrepancies with previous studies that generally included smaller numbers of patients and used non-uniform criteria for diagnosing AM. Some reports included only patients with histologically proven AM whilst others enrolled cases of suspected AM selected only on the basis of CMR criteria.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As supporting independent data, a Finnish study on childhood myocarditis also demonstrated relative low occurrence of in-hospital death and HTx (1.9%) among all children admitted with AM. 29 Differences in patient cohorts and study design may explain, at least in part, the discrepancies with previous studies that generally included smaller numbers of patients and used non-uniform criteria for diagnosing AM. Some reports included only patients with histologically proven AM whilst others enrolled cases of suspected AM selected only on the basis of CMR criteria.…”
Section: Discussionmentioning
confidence: 96%
“…They observed that the prevalence of male sex increased with age, and in children aged 11 to 15 years the prevalence of males was 80%. 29 Another study focusing on the outcome of patients with pericarditis, reported the prevalence of male sex was around 80% in those with myocarditis associated with pericarditis (myo-pericarditis or peri-myocarditis) compared with individuals with isolated pericarditis where the prevalence of male sex dropped to 54%. 39 Similarly, in 2 other studies on AM diagnosed by CMR with median LVEF above 55%, the prevalence of male sex was 77% and 76% respectively.…”
Section: Figure 3)mentioning
confidence: 99%
“…Previous research investigating epidemiology of pediatric myocarditis was based on Western population. 1) Our study is the first nationwide epidemiological study to investigate acute myocarditis in Korean children. Furthermore, our study provides comprehensive data regarding the demographic features and management of acute myocarditis in children over a 10-year period.…”
Section: Discussionmentioning
confidence: 97%
“…A nationwide study in Finland reported an incidence rate of 1.95 cases/100,000 person-years in children aged 0–15 years. 1) A Japanese study (based on questionnaires mailed to teaching hospitals) reported an incidence rate of 0.26 cases per 100,000 populations among children and adolescents aged 1 month–17 years. 2) Notably, the reported incidence rate varies significantly across studies, 4) 5) and the true incidence rate of acute myocarditis in children remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation